2021
DOI: 10.3389/fsoc.2021.618210
|View full text |Cite
|
Sign up to set email alerts
|

Pivoting to Childbirth at Home or in Freestanding Birth Centers1 in the US During COVID-19: Safety, Economics and Logistics

Abstract: Birth-related decisions principally center on safety; giving birth during a pandemic brings safety challenges to a new level, especially when choosing the birth setting. Amid the COVID-19 crisis, the concurrent work furloughs, business failures, and mounting public and private debt have made prudent expenditures an inescapable second concern. This article examines the intersections of safety, economic efficiency, insurance, liability and birthing persons’ needs that have become critical as the pandemic has rav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…65 Accordingly, our findings can inform the development of a patient decision aid to help support women and birthing people consider the risks and benefits, as well as personal values and expectations, associated with various birth settings. 27 Concerns about COVID-19 transmission in hospitals have prompted renewed exploration of birth center and home birth options and analysis of the costs of providing perinatal care in high-risk, high-intervention settings, 20,66,67 increasing the need for a decision aid aimed at supporting birth setting decision making.…”
Section: Discussionmentioning
confidence: 99%
“…65 Accordingly, our findings can inform the development of a patient decision aid to help support women and birthing people consider the risks and benefits, as well as personal values and expectations, associated with various birth settings. 27 Concerns about COVID-19 transmission in hospitals have prompted renewed exploration of birth center and home birth options and analysis of the costs of providing perinatal care in high-risk, high-intervention settings, 20,66,67 increasing the need for a decision aid aimed at supporting birth setting decision making.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Our findings also support other studies that show how COVID‐19 has affected patients' decisions about place of birth, in that more pregnant patients are considering community birthing models such as home birth because of concerns related to hospital safety and undesirable visitation policies during the pandemic. 22 , 23…”
Section: Discussionmentioning
confidence: 99%
“…We also believe that US community midwives can seize this pandemic moment to raise national awareness of their value, while obstetricians can become more aware and accepting of the high value and cost-savings of midwifery care and community births. In an analysis comparing the costs of in-vs out-of-hospital births, which also provides ample evidence of the safety of CPM-attended community births, Anderson, Daviss, and Johnson (2021) have shown that, if only 10% more US births took place at home or in freestanding birth centers, the cost-savings would amount to $11 billion , along with improved birth outcomes-or $321 million per percentage raise.…”
Section: Conclusion: Negotiating Integrated and Sustainable Maternity...mentioning
confidence: 99%